AromaDb: A Database of Medicinal and Aromatic Plant’s Aroma Molecules With Phytochemistry and Therapeutic Potentials - Kumar, Yogesh; Prakash, Om; Tripathi, Himanshu; Tandon, Sudeep; Gupta, Madan M.; Rahman, Laiq-Ur; Lal, Raj K.; Semwal, Manoj; Darokar, Mahendra Pandurang; Khan, Feroz (Frontiers in Plant Science, 2018)
In traditional medicine, herbal medicine and aromatherapy, use of essential oils and their aroma compounds have been known since long, for the management of various human diseases. The essential oil is a mixture of highly complex, naturally occurring volatile aroma compounds synthesized by medicinal and aromatic plants as secondary metabolites. Essential oils are widely used in pharmaceutical, cosmetic, sanitary, food industry and agriculture for their antibacterial, antiviral, antifungal, antiparasitic, insecticidal, anticancer, neuroprotective, psychophysiological and antiaging activities. Aroma (volatiles) compounds comprise a chemically diverse class of low molecular weight organic compounds with significant vapour pressure. However, aroma compounds produced by plants, mainly attract pollinators and seed dispersers and provide defence against pests and pathogens. In humans, about 300 active olfactory receptor genes are involved to detect thousands of different aroma molecules and modulates expression of different metabolic genes regulating human psychophysiological activity, brain function, pharmacological signalling and therapeutic potential. Keeping in mind this importance, present database, namely, AROMA (http://bioinfo.cimap.res.in/aroma/) covers information of plant varieties/chemotypes, essential oils, chemical constituents, GC/MS data, yield, aroma compounds, fragrance type, toxicological and ecological information, effected human genes, and bioactivity details. The Database includes 1321 aroma compound chemical structures, bioactivities of essential oil/aroma compounds, 357 fragrance type, 166 commercially used plants, and their high yielding 148 varieties/chemotypes. Also includes calculated cheminformatics properties related to identification, physico-chemical properties, pharmacokinetics, toxicological, and ecological information. Also includes interacted human genes affecting various diseases related cell signalling pathways correlating the use of aromatherapy. This database will benefit researchers who wish to explore the potential of essential oils and aroma compounds in the development of novel formulations against human diseases.